Sistrunk’s operation: Ten years’ experience in a teaching hospital - Koirala, Krishna Prasad (Nepal Journal of Medical Sciences, 2020)
Introduction: Thyroglossal duct cyst (TGDC) is a congenital condition that results from persistence of thyroglossal duct. It commonly presents in the midline neck as a painless nodule. On physical examination, it moves with protrusion of tongue and on swallowing. Meticulous clinical history and physical examination are sufficient to make a correct preoperative diagnosis. Ultrasonography of the neck and fine needle aspiration cytology are other useful tools in the diagnosis. Although a congenital anomaly, it usually presents in the first and second decades of life. The standard treatment of choice for thyroglossal duct cyst is Sistrunk’s operation. The aims of this study are to identify the age of presentation of patients with thyroglossal cyst, its site of occurrence in relation to hyoid bone and to look for the patterns of recurrence after Sistrunk’s operation. Methods: This is a retrospective study with 34 patients over a period of ten years operated by a single surgeon. Patients treated by Sistrunk’s operation and confirmed as the thyroglossal duct after histopathology report were included in the study. Their demographic data, age at presentation, surgical treatment and recurrence rate were noted and analysis were made. Results: There was slight male predominance, majority of the thyroglossal cysts were found in the pediatric population and below the hyoid bone, and there were acceptable recurrences. Conclusions: Thyroglossal duct cyst is a disease of children. Sistrunk’s operation is the standard surgical procedure with minimal recurrence.